PEMBERDAYAAN ANGGOTA SEKOPER MENJADI “CREATIVEPRENEUR HEALTHY FOOD” BERBASIS POTENSI PANGAN LOKAL DI DESA KRAMATINGGIL KABUPATEN GRESIK - Ariestiningsih, Eka Srirahayu; Has, Dwi Faqihatus Syarifah; Ningrum, Diana Oktavia (Jurnal Pengabdian dan Kewirausahaan, 2021)
Sekolah Perempuan (SEKOPER) is a program initiated by the Gresik Regency Government in collaboration with UN Women Australia. This program is a forum for village women to exchange knowledge and experiences, identify women's needs and interests to improve their quality of life. The impact of the COVID-19 pandemic does not only attack clinically but also worsens the economic side of the community, including Kramatinggil Village, which is in the Kebomas District, Gresik Regency, East Java Province. The purpose of this community service activity is to improve the quality of life of women in Kramatinggil village which is still low by producing aloe vera, temulawak and moringa which are local food potentials in the village so that they can increase economic and health values and form creativepreneur healthy food. The first stage is counseling about creativepreneur to SEKOPER members. The second stage is counseling about the benefits of aloe vera, temulawak and Moringa leaves. The third stage is counseling and the practice of making healthy food/snack products from aloe vera, temulawak and Moringa leaves The establishment of creativepreneur healthy food from SEKOPER members and the launch of the product "Dayya Ummat" in collaboration with the University of Muhammadiyah Gresik and the village of Kramainggilt. The outputs of this community service are: 1) Health Healthy food products such as: Aloe Vera Sticks, Temulawak Cookies and Moringa Tea, 2) Forming SEKOPER members as Pioneers of creativepreunur Healthy food in Kramatinggil Village, and 3) Launching the "Dayya Ummat" product in collaboration with the University Muhammadiyah Gresik and Kramatinggil Village.